Differential Strain Analysis: An Investigation Over Its Feasibility For Determining Coal’s Cleat Orientation - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2010)
Gas production from coal bed methane (CBM) has been rising as supplement to conventional gas reservoirs. Effective CBM production is much determined by well placements with regards to orientation of the coal reservoir’s face cleat. This is true since this cleat type provides the main path of fluid migration from storage to wellbore. It is therefore imperative to understand and determine the general orientation of the cleats of concern. This information is usually obtained from visual description on core samples, and whenever available from analogy to outcrop data. This is considered as insufficient and a means for studying core sample’s interior is required in order to ensure consistency between external and internal appearances. This paper presents an investigative study over the possibility of differential strain analysis (DSA) technique to serve the purpose. The technique is normally used for measuring subsurface in situ stress field, and through the use of a similar basic concept it is proposed to be used for determining orientation of face cleats in coal samples. The study includes utilization of DSA data obtained from measurements on samples taken from great depths. Review and re-working over the data has shown that the technique can well indicate the orientation of face cleats. A general orientation over all tested samples is also indicated with reasonable degree of reliability. This leads into conclusion that the DSA technique can be well used to indicate cleat orientation and therefore help in better characterizing coal.